Interpretation of Legal Norms. Text vs Law - Zarikyan, K. (Bulletin of Yerevan University C: Jurisprudence, 2020)
In the article different mechanisms of legal norms’ interpretation are being compared. As a result, many disadvantages of the textualism are being discovered and the author offers a thesis that legal norms, governing real human life, should not be interpreted mostly by using linguistic rules. Ultimately, no matter how varied the possible written and unwritten rules of interpretation, however, it is a question of law, and therefore the choice of law enforcement should be determined not by textual-linguistic, but legal representations of the latter. It is necessary to exclude the fatal mistakes that often arise due to the superiority of the scales in favor of a textual rather than legal interpretation. It is stated that it is the legal interpretation that reveals the initial will of the legislator.
Keywords: linguistic rules of interpretation, textualism, standart picture, legal mechanisms of interpretation, legal construction, will of legislator